CHANGES IN THE POLITICAL AND LEGAL VIEWS OF THE NATIONAL ELITE AFTER THE HETMANATE ACCESSION TO THE RUSSIAN STATE (LATE XVII-XVIII CENTURY - Стенгач, Надія (SWorldJournal, 2025)
Following the incorporation of the Hetmanate into the Moscow Kingdom in 1654 (an event that was facilitated by the Pereyaslav Treaty), there was a considerable shift in the political and legal culture of the Cossack officers. This was due to the gradual